Explaining benefit take-up behavior: The role of incentives and habits - Olof Rosenqvist; Håkan Selin (Institute for Evaluation of Labour Market and Education Policy (IFAU), 2023)
Take-up of social benefits is a central issue in poverty alleviation and fiscal evaluations of policy reforms. However, it is difficult t o fi nd exogenous variation in the benefit level, and little is therefore known about takeup responses to basic financial i ncentives. We exploit large and plausibly random variation in levels of "flat rate parental leave benefits", which all Swedish parents are entitled to. There are no financial r easons t o leave money on the table, but take-up is nevertheless imperfect. Higher benefits substantially increase claiming across the income d istribution. We further detect sizeable spill-over effects on subsequent take-up of low-income earners.
Keywords: H24; J22; 330; Parental benefits; incomplete take-up; after-tax benefits